Coatings Based on Essential Oils for Combating Antibiotic Resistance - Anita Ioana Visan; Irina Negut (MDPI AG, 2024)
In the current era of widespread antimicrobial resistance, the utilization of essential oils (EOs) derived from plants has emerged as a promising alternative in combating pathogens that have developed resistance to antibiotics. This review explores the therapeutic potential of essential oils as valuable tools in restoring the efficacy of antibiotics, highlighting their unique ability to affect bacteria in multiple ways and target various cellular systems. Despite the challenge of elucidating their precise mode of action, EOs have shown remarkable results in rigorous testing against a diverse range of bacteria. This review explores the multifaceted role of EOs in combating bacterial microorganisms, emphasizing their extraction methods, mechanisms of action, and comparative efficacy against synthetic antibiotics. Key findings underscore the unique strategies EOs deploy to counter bacteria, highlighting significant differences from conventional antibiotics. The review extends to advanced coating solutions for medical devices, exploring the integration of EO formulations into these coatings. Challenges in developing effective EO coatings are addressed, along with various innovative approaches for their implementation. An evaluation of these EO coatings reveals their potential as formidable alternatives to traditional antibacterial agents in medical device applications. This renaissance in exploring natural remedies emphasizes the need to combine traditional wisdom with modern scientific advancements to address the urgent need for effective antimicrobial solutions in the post-antibiotic era.